An obstetrician's own experience of having an extremely preterm baby: an autoethnography - Mangla, Mishu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Parental stress after the birth of a preterm baby is well known. Being an obstetrician who herself had an extremely premature delivery, the author thought of narrating self-experience regarding delivering a preterm baby. The objective is to engage the reader both cognitively and emotionally regarding aspects of preterm birth that obstetricians often disregard. Autoethnography is a unique form of research that examines an interplay between self and cultural norms. The role of narrating self-experience by the author, though well established in mental health issues, has not been explored much in maternal and child health. Mothers of preterm babies go through a mixed bag of feelings. The feelings of happiness and delight are in no time transformed into anxiety, guilt, sufferance, and sometimes even frank depression. Preventing preterm births as far as possible should be the goal of every obstetrician.